Effect of Rotation Speed and Flow Rate on Slip Factor in a Centrifugal Pump - Bo Chen; Baolin Song; Bicheng Tu; Yiming Zhang; Xiaojun Li; Zhigang Li; Zuchao Zhu (Shock and Vibration)
This work analyzes the causes of the slip phenomenon in the impeller on the basis of the internal flow mechanism. Detailed optical measurements of the flow inside the rotation passages of a five-bladed centrifugal pump impeller are obtained through particle image velocimetry (PIV). On the basis of experimental data, the deviation coefficient of slip velocity is proposed and then revised according to the slip factor calculation formula of Stechkin. Results show that, at the same rotation speed, the slip factor increases with the flow rate and reaches the maximum value at 1.0 QBEP flow rate. At different rotation speeds, the slip factor increases with the rotation speed and shows a relatively large variation range. Moreover, a revised slip factor formula is proposed. The modified model is suitable for the correction of slip factor at part-load flow rates and serves as a guide for the hydraulic performance design and prediction of centrifugal pumps.